PROTEIN CONSUMPTION, ANEMIA, AND SLEEP QUALITY AS DETERMINANTS OF NUTRITIONAL STATUS IN ADOLESCENT GIRLS - Wazha Lidini Hanifah; Tria Astika Endah Permatasari (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
This study aims to investigate the relationship between protein intake, anemia, and sleep quality on the nutritional status of adolescent girls at Pondok Pesantren Bani Tamim. The research design is cross-sectional, involving a sample of 70 randomly selected adolescent girls. Data collection was conducted using the Food Frequency Questionnaire (FFQ) to assess food intake and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. The Chi-Square statistical analysis revealed a significant association between animal protein intake and nutritional status (p=0.003), whereas no significant link was identified between plant protein intake and nutritional status (p=1.000). The study also found no significant relationship between anemia and nutritional status (p=1.000). However, sleep quality showed a significant association with nutritional status (p=0.005), with most over-nourished adolescents sleeping less than 5 hours per day. Lack of sleep can disrupt hormonal regulation that controls appetite, increasing the risk of obesity. The low intake of animal protein at the boarding school was due to the limited supply of animal-based foods, while the adolescents tended to consume plant-based proteins such as tofu and tempeh. These findings highlight the importance of increasing animal protein intake and improving sleep quality to support optimal nutritional status in adolescent girls.